SOSIALISASI PENERAPAN SAFETY RIDING BERKENDARA DI JALAN RAYA BERSAMA UNIVERSITAS PENDIDIKAN NASIONAL - Mahadewi, Kadek Julia; Tri Wulandari, Ni Gusti Agung Ayu Mas; Nandari, Ni Putu Sawitri; Prasada, Dewa Krisna; Rama, Bagus Gede Ari (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
Increasing the number of accidents every year in Indonesia has forced the government to make efforts to reduce the number of accidents that result in the loss of someone's life. The government, by using the Safety Riding method in driving on the highway, hopes to reduce the number of accidents that occur in the community by paying attention to completeness and safety in traffic on the highway. As for the problems that arise, how is Safety Riding implemented in rescue efforts in society? The aim of community service is through socialization carried out by the community, especially the younger generation, to be able to have awareness of driving on the highway by remembering the importance of safety for themselves and others as well as feeling safe and comfortable when driving. The use of Safety Riding cannot be separated from the role of the Government, Companies and the community in forming synergy in efforts to save traffic. The implementation of Safety Riding is present in society to prevent the number of accidents so that UULLAJ is implemented as a suggestion for legal protection in society.